Efektivitas Tahapan Proses Pengambilan Keputusan dalam Program Inovasi Pembelajaran Kurikulum Merdeka Belajar di SMA N 10 Kota Bengkulu - Irpini Hayati; Nurul Khofifah; Alfauzan Amin (Departement of Mathematics Education, 2023)
This paper aims to find out the independent learning curriculum and the stages of the innovation decision-making process in the independent curriculum and independent learning curriculum innovations. This research method uses non-quantitative qualitative. This research method is library research. The approach is carried out by analyzing and interpreting theoretical matters related to research. Data sources were obtained from various books, journals and the internet, as well as other relevant sources. Where researchers try to uncover and explore about 1) the Independent Curriculum Innovation Process Model; and 2) the implications of the independent curriculum for students and teachers in Indonesia in the 21st century through literature/library analysis. The results of this study are: The Independent Curriculum Innovation Process Model is carried out through reducing Basic Competency for each subject so that teachers and students can focus more on essential competencies for continuing learning at the next level, where the essence of independent learning is the freedom of teachers and students in the learning process. Meanwhile, the implications of the independent curriculum for students and teachers in Indonesia are related to the characteristics used in this curriculum, namely students and teachers jointly carrying out project-based learning to develop soft skills and character according to the Pancasila student profile, where the focus is on essential material so that there is time to in-depth learning for basic competencies including: literacy and numeracy.